Does Financial Flexibility foster Investment Efficiency? Evidence from an Emerging Market - Islam, Md. Rashidul; Hossain, Monirul Alam; Uddin, Mohammad Shamsu; Bahta, Dawit Teclemariam (Asian Business Review, 2020)
This research aims to examine the relationship between financial flexibility and investment efficiency empirically, i.e., how financial flexibility effects suboptimal investments and efficiency. To attain the research objectives, we used panel data for 18 years (2000-2017) obtained from the CSMAR database; and also used the GMM estimation technique for research outcome. Our empirical results reveal that financial flexible firms can reduce the suboptimal investment by increasing investments compared to the inflexible firms and increases the investment efficiency. Also, financially flexible firms generate additional power to borrow external finance by showing a significant positive relationship with current and expected leverage. This research considers China as an emerging economy that is in the transition of being a developed country with a unique set of corporate governance, which ensures the independence of independent directors by providing authority to disclose important board decisions to the public. Besides, the governance system is highly monitored by the government, which in turn reduces and information asymmetry and enact to provide investment efficiency. Thus, the outcome of this research offers several conceptions for researchers and managers, which may be useful for both emerging and advanced countries. The results indicate that financial flexibilities lead to excess debt capacity, and this capacity can be used in the bad time when external financing is challenging to fund profitable projects, and also financial flexibility can be used to exploit lucrative projects and reduce the underinvestment or overinvestment entailing investment effectiveness. Previous research addresses the issue related to cost and benefit, information asymmetry, ownership concentration, and firms’ propensity to financial flexibility. A little research conducted on financial flexibility and investment efficiency in the developed market (in Europe and USA), and thus the issue of and financial flexibility measured in unused debt capacity and investment efficiency, is one of the fundamental research in the emerging economy.